2022
DOI: 10.3389/fphar.2022.799338
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Drug Treatments and the Incidence of Liver Injury in Hospitalized Patients With COVID-19

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) has led to the emergence of global health care. In this study, we aimed to explore the association between drug treatments and the incidence of drug-induced liver injury (DILI) in hospitalized patients with COVID-19. A retrospective study was conducted on 5113 COVID-19 patients in Hubei province, among which 395 incurred liver injury. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated by Cox proportional hazards models. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…Previous studies showed that remdesivir was associated with liver injury in COVID-19 patients [ 26 , 27 , 28 ]. Moreover, Gao and colleagues reported that COVID-19 patients receiving corticosteroids had an increased risk of drug-induced liver injury (DILI) in contrast to non-user COVID-19 patients [ 29 ]. Therefore, in our dataset, patients receiving remdesivir or steroids were mostly patients in GROUP A ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that remdesivir was associated with liver injury in COVID-19 patients [ 26 , 27 , 28 ]. Moreover, Gao and colleagues reported that COVID-19 patients receiving corticosteroids had an increased risk of drug-induced liver injury (DILI) in contrast to non-user COVID-19 patients [ 29 ]. Therefore, in our dataset, patients receiving remdesivir or steroids were mostly patients in GROUP A ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired liver function in the elderly increases the drug concentrations in their livers. The decline in liver function also explains the higher incidence of DILI in the elderly[ 105 ]. Therefore, intensive liver function monitoring should be considered for patients treated with drugs such as remdesivir, LPV/v, and tocilizumab.…”
Section: Liver Manifestations Associated With Covid-19mentioning
confidence: 99%
“…Поражение печени, возникающее у части пациентов при коронавирусной инфекции, зависит от возраста, географического региона, тяжести протекания COVID-19 в целом и ряда других обстоятельств. Печень является основным органом метаболизма и детоксикации; таким образом, поддержание здоровой функции печени имеет решающее значение для эффективности и переносимости разных схем лечения COVID-19 [25].…”
Section: механизмы повреждения печени при Covid-19unclassified
“…Между пациентами, которые использовали, и теми, кто не использовал эти препараты, наблюдалась достоверная разница в частоте развития лекарственной гепатопатии (p < 0,05). Пациенты, которые получали гидроксихлорохин/хлорохин 362 (95,26%) и ТКМ 3234 (92,77%), реже имели острое повреждение печени [25].…”
Section: механизмы повреждения печени при Covid-19unclassified